Evaluation of the Impact of Hybrid Working on Auditors' Self-Efficacy - Larasati, Bethari; Fatima, Eliza (East Asian Journal of Multidisciplinary Research, 2023)
This study aims to evaluate the concept of hybrid working in Public Accounting Firms (KAP) and its impact on self-efficacy after the COVID-19 pandemic who previously worked remotely. This research was conducted using a qualitative research method. The data source of this research was carried out by distributing questionnaires with 53 respondents from associate to manager level who work at Public Accounting Firm and interviews with 5 resource persons from senior associate to manager level from Big Four and Non-Big Four Firms. The results showed that in implementing the hybrid concept, Firms has disseminated the Firms' policy, provided support, provided facilities for collaboration and focus, as well as provided flexibility in determining work schedules. Self-efficacy arising from hybrid working shows experience, expertise, confidence, motivation, and auditor performance help auditors adapt to hybrid work. For this reason, this study recommends that the hybrid working model can be continued as a new working trend of auditors in KAP. This research is still limited to auditors below manager level and does not represent all KAP in Indonesia. This research provides an understanding of the concept of hybrid working which is a new work style choice in the auditor environment by looking at the auditor's personal self-efficacy.